Antioxidant Activity of Ethanol Extract on Qust Al Hindi (Saussurea lappa) Roots Using the FRAP Method - Putry, Dhevy Try; Syarif, Sukmawati; Rahmawati, Rahmawati (Universitas Muslim Indonesia, 2024)
Qust al hindi (Saussurea lappa) is a plant that has antioxidant activity, especially in the roots. Qust al hindi contains several chemical compounds including flavonoids, steroids, terpenes, alkaloids, sesquiterpenes, costunolide, dehydrococtus lactones, cynaropicrin, and chlorogenic acid. This study aims to determine the antioxidant activity of the ethanol extract of qust al hindi root using the FRAP method. Samples that had become powder were extracted using the soxhletation method with 96% ethanol and obtained a % rendition of 5.302%. The extract obtained was measured using a UV-Vis spectrophotometer at a maximum wavelength of 718 nm after being mixed with several FRAP reagents, using a quercetin standard. The results of the antioxidant analysis showed that the average antioxidant activity of the ethanol extract of the qust al hindi root (Saussurea lappa) using the Frap method was 10.3671 mgQE/g extract. Which means that the antioxidant activity of each g of extract is equivalent to the antioxidant activity of 10.3671 mg of quercetin.